FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN LAYANAN BPJS DI RUMAH SAKIT UMUM DAERAH PADANG LAWAS UTARA - tiasapohan; Johan Saputra (Poltekkes Kemenkes Medan, 2023)
Health is a right for every citizen regardless of social, economic, gender, race and religion status. In Declaration of health stated that health is the most basic human right of every human being in the world (Alma, 2017). BPJS Health is a legal entity that is directly responsible to the President for managing health insurance for all Indonesian people (Ministry of Health, 2020). The health service delivery system in the world today can be thought of as a continuum that places the institutional-universal system at one point with residual-selective at another point. The method is quantitative research with using a cross sectional approach. The population is all BPJS participants in the North Padang Lawas regional general hospital. Sampling used the accidental sampling method of 94 people. The results of the research show that there are many factors relating to knowledge, such as; attitudes, distance, availability of facilities and infrastructure, information and health workers with the utilization of BPJS services at the North Padang Lawas Regional General Hospital. The Conclusion is most significantly related to the utilization of BPJS services at the North Padang Lawas regional general hospital is the Attitude factor